IT Governance Evaluation of Hospital Information Systems Using Framework: Case Study of RSUD Welas Asih - Muhammad Hanif Zahran; Sinung Suakanto; Basuki Rahmad (Vifada Management and Social Sciences, 2026)
Purpose: This study evaluates the governance capability of the Hospital Management Information System (Sistem Informasi Manajemen Rumah Sakit/SIMRS) at RSUD Welas Asih using COBIT 2019 and formulates improvement directions to strengthen service reliability. Research Design and Methodology: This study applies an evaluative case study with a mixed-method approach. Data were collected through a structured questionnaire completed by ten respondents from the SIMRS Installation, an interview with the Head of SIMRS Installation, direct observation, and limited document analysis. COBIT 2019 was used to assess selected APO, BAI, and DSS processes, while triangulation was applied to interpret questionnaire results against interview and documentary evidence. Findings and Discussion: The questionnaire results show generally positive perceptions of SIMRS governance, especially in strategic alignment, user-driven development, and operational support. However, triangulation identifies improvement needs in periodic training, user adaptation after feature changes, change documentation, external system dependency, incident handling, manual fallback, data re-entry, BPJS claim validation, and infrastructure resilience. Implications: The study recommends strengthening competency development, formal change logs, incident escalation, fallback procedures, data reconciliation, infrastructure continuity, and continuous governance monitoring.